Determination Rice Husk Amorphous Silica In Alor District As An Additive On The Manufacture Of Composite Portland Cement - Loth Botahala (Fakultas Teknik, Universitas Katolik Widya Mandala Surabaya, 2020)
Research on the determination of amorphous silica in Alor rice as an additive in the manufacture of portland composite cement has been carried out. The aim this to determine the concentration of amorphous silica in the form of oxides in rice husk ash with variations in time and combustion temperature. Washed rice husks are heated in an oven at 100 °C for 24 hours. After that rice husk is heated in the furnace with variations in temperature and time. Rice husk ash originating from the furnace combustion is then cooled for 24 hours and smoothed in a blender for 3 minutes, then sifted on the number size 230 sieve and analyzed using X-RD and X-RF. X-RD results showed that the rice husk ash samples were amorphous with the name Chitopentaose caprate (C200H363N5O38). While the results of X-RF at combustion with a temperature of 700 °C and time of 4 hours obtained amorphous silica at 97.50% with a very low CaO concentration of 0.467%.